Nazi architects of the Holocaust - Brezina, Corona (Documentary history of the Holocaust., 2015)
Explores the history of the Holocaust in Germany, covering the ideology behind it, the rise of the Nazi party, the men given the task of implementing it, the extermination in the East, and the systematic extermination in the death camps.